La profilassi antibiotica nelle fratture esposte: la proposta per un nuovo PDTA - Zamparini, E.; Castiello, E.; Marchionni, E.; Rossi, N.; Fornaro, G.; Pugnetti, C.; Tigani, D.; Viale, P. (Lo Scalpello - Journal, 2019)
ANTIBIOTIC PROPHYLAXIS IN OPEN FRACTURES: OUR PROPOSAL FOR A NEW DIAGNOSTIC-THERAPEUTIC PROTOCOLAs shown by the studies of Gustilo–Anderson, infections are one of the most frequent complications in open fractures, owing to the heavy contamination of tissue during the trauma. Therefore, an immediate antibiotic prophylaxis capable of covering the majority of microbes involved in this type of contamination is needed. In this paper we address this need by proposing a diagnostic-therapeutic protocol.